Pemanfaatan Ubi Hutan dengan Pengawet Alami Sebagai Alternatif Diversifikasi Pangan pada Masyarakat Kabupaten Buton - Jaya, Evie Fitrah Pratiwi (Jurnal Gizi Ilmiah, 2014)
Utilization of cassava using natural preservatives as an alternative to local food development on Mawasangka Island, Buton Regency, Southeast Sulawesi (supervised by Suryani A. Armyn and Nurhaedar Jafar). This study aims to obtain dodol products from forest cassava using natural preservatives as an alternative to local food development. The type of research used is an experiment with a laboratory analysis design. The research was carried out in 3 stages, the first stage was conducting preliminary research by testing recipes and organoleptic tests, preliminary research of the product was carried out by proximate analysis and the final research of the product was carried out by microbial analysis according to SNI. The results of the research. The DIII dodol formula gave a good level of preference. For the initial research product, namely proximate analysis, the selected formula was 7.50% for crude protein and 7.94% for the control formula, crude fat was 0.46%, the selected formula was 0.42% for the control formula, Carbohydrate 71.37% selected formula and 71.27% control formula, water content 19.48% selected formula and 19.25% with max.20% SNI requirements, 1.42% ash content selected formula, 0.83% for dodol control, the minimum SNI requirement is 7%, the fiber content of the selected dodol is 1.40% and 0.14% for the control dodol. In the final study of the product, there were differences in the microbiological quality of the types of microbes, namely the selected dodol contained yeast microbes so that it looked normal to the naked eye, while the control dodol contained mold types, which could make the product unfit for consumption. The final product research, the shelf life of the selected dodol product is 12 days, while the control dodol lasts 6 days